Measurement of Variables in Entrepreneurship Intention Studies: A Review of the Entrepreneurship Intentions Questionnaire (EIQ) - Mwange, Austin (IJRDO - Journal of Social Science and Humanities Research, 2018)
This is article is a review of literature on the measurement of variables in entrepreneurship intentions studies, particularly, the Entrepreneurship Intentions Questionnaire (EIQ). The features of the EIQ have been presented. Further, selected empirical studies that have applied the EIQ in student entrepreneurship intentions studies are the cornerstone of this literature review. Furthermore, the article gives a brief analysis of contradictions on measurement of entrepreneurial intentions.